Gamificação, modelo de metodologia de ensino: uma revisão sistemática - Gonçalves, Álvaro Batista (Brasil, 2024)
Introduction: With the great growth of games in all formats, and over the years their population of players increases at the same time as their players grow older, it would become common to use the “idea” that the game passes on to its players . However, it is necessary to identify your “ideas”, contextualize them, conceptualize them and classify them in order to facilitate their use as an action methodology. Therefore, it is necessary to understand: the public that uses games daily in their lives (whether in electronic, physical or methodological format), its origin and how it is present in society (which explain the current scenario of popularity), how technological growth is used to gain more space and how it could be used as an engaging methodological mechanism for the new generations who live with it daily and sometimes don't even realize such a creation formula. Given this, it is necessary to adapt to your school environment and engage students to participate in physical education classes, demonstrating new forms of games and scoring. Objective: to present scientific evidence on the use of gamification as an engaging teaching methodology for students who have difficulty participating in Physical Education classes. Methods: A systematic literature review was carried out through searches in the Pubmed, Google Academic and Bireme-BVS databases, etc. The inclusion criteria consisted of studies that presented Gamification as a teaching methodology in Physical Education classes. Results: 84 articles were found, 18 were excluded because they were applications and did not focus on methodological use in the classroom but rather on the acquisition/improvement of something specific, 15 were excluded because their main objective was engagement/motivation of physical activity in general and not only at school level, thus having a lack of control supervised by teachers, 23 were excluded because they focused on another age group (university students or workers) and not schoolchildren, 17 were excluded because they focused on another subject and not only in physical education, 13 were readable, being classified into Exergames, Motivational with learning, Users of TIDCs (digital information and communication technologies). Conclusion: Therefore, the results of this review were that the use of electronic games, as a pedagogical tool, through active methodologies: exergames and gamification are of great value for physical education classes, as they bring several benefits to building spaces of I teach more dynamic, enjoyable and engaging learning for our students.